Handbook of research on optimizing healthcare management techniques - Wickramasinghe, Nilmini (Advances in healthcare information systems and administration (AHISA) book series., 2020)
"This book provides an extensive and rich compilation of various ICT initiatives and examines the role that ICT plays and will play in the future of healthcare delivery"--Provided by publisher.